Comparing peri-operative complications of paediatric and adult anaesthesia: A retrospective cohort study of 81 267 cases. Issue 4 (April 2018) - Westerkamp, Andrie C.; de Geus, A. Fred; Molenbuur, Bouwe; Meyer, Peter; Wietasch, J.K. Götz; Struys, Michel M.R.F.; Hendriks, Herman G.D.
Abstract : BACKGROUND: Comparisons of peri-operative complications associated with paediatric (⩽16 years) and adult anaesthesia are poorly available, especially in which cardiac surgery, organ transplantation and neurosurgery are involved. OBJECTIVE: The aim of this study was to evaluate the nature and incidence of peri-operative complications that might be due to anaesthesia and to identify independent risk factors for complications in children and adults, including those undergoing cardiac surgery, organ transplantation and neurosurgery. DESIGN: Retrospective cohort study. SETTING: The study was performed at the University Medical Centre Groningen in the 4 years between 1 January 2010 and the 31 December 2013. MAIN OUTCOME MEASURES: Complications and their severity were graded according to the standard complication score (20 items) of the Dutch Society of Anaesthesia. Univariate and multivariate regression analysis was used to identify independent risk factors for the reported complications. RESULTS: A total of 81 267 anaesthetic cases were included. In the paediatric cohort, there were 410 (2.9%) complications and 1675 (2.5%) in the adults. In both cohorts age, American Society of Anaesthesiologists classification and emergency treatment were independent risk factors for complications. With respect to age, infants less than 1 year were at the highest risk, whereas in the adult cohort, increased age was related to a greater number of complications. The incidences of the specific complications were different between both cohorts. Upper airway obstruction was more frequently observed in paediatric patients (26%), whereas in the adults, complications with the highest incidence concerned conversion of regional-to-general anaesthesia (25%) and hypotension (17%). CONCLUSION: Risk factors for all peri-operative complications were similar for paediatric and adult anaesthesia. However, the incidence of specific complications differed between both age categories.